Time Sensitive Networking for Wi-Fi Based Wireless Industrial Environments - Kinabo, Arnold Baraka Doste (Department of Electrical Engineering, 2022)
In production industries, mission-critical assignments require networks characterised by deterministic low latency, dedicated bandwidth resources, and, chiefly, reliability. Several fieldbus technologies are specially placed for this. Their commonality is that they run on standard Ethernet. The relatively new Time Sensitive Networking (TSN) is among these technologies. It is a set of Ethernet standards that guarantees determinism for real-time usecases. TSN sets itself apart in that it is vendor-agnostic. And so, it promotes interoperability among standard-conformant devices. Being based on Ethernet, even TSN is plagued by downsides associated with cabled networks, most importantly, the limited range and mobility. In this regard, wireless networks are an attractive option – it would be an opportunistic venture to operate TSN in the wireless medium. Previous works have tried to address how this can be done, but as yet, it is an open problem. The issue is that most wireless networks are not optimised for determinism. Most lack the scheduling, synchronisation and other capabilities that timing-stringent applications require. Wi-Fi, for instance, suffers from many issues stemming from randomised medium access and interference, which remove the predictability from its communications. Critical TSN traffic needs special consideration when run with other services in current Wi-Fi. That being said, the key research question is: can one contend with the problem of transmitting TSN and non-TSN traffic together in the same wireless network? To answer this, the work develops a TSN simulation model that operates in Wi-Fi, whose test results can be studied to aid in analysing wireless TSN. The prototype model runs in a simulation environment, and was developed using methods that involved reusing and modifying the present wireless architecture to support the TSN traffic. Through the course of several iterative experiments, it was revealed that although the current generation of Wi-Fi can support TSN traffic, it does so inefficiently. Even with no interference, the TSN traffic experiences low losses only when the network capacity utilisation is very low, below a small percentage value. Considering the typically low demands on bandwidth in many TSN applications, this inefficient operation may still be sufficient for operating TSN over existing Wi-Fi networks. For more robust and general applications, Wi-Fi requires further enhancements to its mode of operation in order to support prioritisation of TSN traffic and more accurately cope with higher loads.